Percepción de la calidad de atención del control Prenatal por la gestante atendida como usuaria Externa en el Hospital II-1 Moyobamba. Julio – Octubre 2015 - Vásquez Rodríguez, Karen Elizabeth (2015)
This study aimed to determine the perception of the quality of prenatal care for Pregnant women served as external user in the Hospital II-1 Moyobamba. July- October 2015 a simple quantitative descriptive cross-sectional study with Prospective data collection was performed. The sample consisted of 157 Pregnant women attended as an external user who attended the obstetrics at the Hospital II-1 - MINSA - Moyobamba that met the inclusion and exclusion criteria. For processing and data analysis, it designed a database in Excel 2010, which Allowed the preparation of simple charts and graphs. The results achieved are: Pregnant served as external would use who received prenatal care at the Outpatient clinic of the Hospital II-1 Moyobamba have the average age of 20-24 Years old; the majority are cohabiting marital status; and most have full secondary Education degree; timeout used for obstetric care in the office 55.4% perceived As fair; 93.6% perceive that they provided information on nutrition during Pregnancy; their treatment during prenatal care, 70.1% said that their treatment Was good; the 62.4% felt that the privacy in the obstetrics clinic was fair; 63.1% Felt that cleaning the obstetrics clinic was good; 66.9% felt that the overall Cleanliness of the hospital was bad; the service provided by the clinical laboratory Is perceived as fair; while the pharmacy service provided is perceived as wrong. Concluding: the perception of the quality of prenatal care for pregnant women Served as external user in Moyobamba Hospital II-1 is regular.